2020
DOI: 10.1016/j.heliyon.2020.e04640
|View full text |Cite
|
Sign up to set email alerts
|

Searching potential antiviral candidates for the treatment of the 2019 novel coronavirus based on DFT calculations and molecular docking

Abstract: In the present work, the succinic acid (SA), L-pyroglutamic acid (L-PGA), N-phenyl-thioacetamide (N-NPTA), 2-amino-5-chloropyridine hydrogen succinate (ACPS), epigallocatechine Gallate (EGCG) or KDH and, selenomethionine (SeM) compounds have been proposed as potential antiviral candidates to treatment of COVID-19 based on B3LYP/6-311++G∗∗ calculations and molecular docking. Solvation energies, stabilization energies, topological properties have been evaluated as function of acceptors and donors groups present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…EGCG is reported to inhibit SARS-CoV-2 3CL-protease using purified SARS-CoV-2 3CL-protease protein [ 7 ]. A computer simulation study also supports that EGCG can block the 3CL-protease activity of SARS-CoV-2 [ [8] , [9] , [10] , [11] ]. In addition, statistical analysis demonstrated that the countries with high green tea consumption showed a striking reduction of COVID-19 risk including morbidity and mortality [ 12 ].…”
Section: Introductionmentioning
confidence: 85%
“…EGCG is reported to inhibit SARS-CoV-2 3CL-protease using purified SARS-CoV-2 3CL-protease protein [ 7 ]. A computer simulation study also supports that EGCG can block the 3CL-protease activity of SARS-CoV-2 [ [8] , [9] , [10] , [11] ]. In addition, statistical analysis demonstrated that the countries with high green tea consumption showed a striking reduction of COVID-19 risk including morbidity and mortality [ 12 ].…”
Section: Introductionmentioning
confidence: 85%
“…The computational approach has been extensively explored in studies of possible drugs against infection by SARS-CoV-2. Sagaama et al [ 27 ] presented results of possible drugs complexed with SARS-CoV-2 proteins using theoretical level DFT and Molecular Docking as well as Jordaan et al [ 28 ] with results involving Simvastatin, Lovastatin, Oxacilin, podophyllotoxin, gefitinib with SARS-CoV-2 main protease. As a consequence, the main goal of this article is to present the result of the study of an interaction between ( R and S )-Linezolid with RBD of SARS-CoV-2 spike protein in complex with human ACE2.…”
Section: Introductionmentioning
confidence: 99%
“…DFT-based optimized geometry allows for the study of frontier molecular orbitals that play an important role in understanding the interaction mechanisms between drugs and their receptors in determining the hit ligands against SARS-CoV-2 [86][87][88][89][90]. The difference between HOMO (highest-energy molecular orbital occupied by electrons) and LUMO (lowest-energy molecular orbital not occupied by electrons) energy values plays a critical role in determining the chemical reactivity, charge transfer capabilities, and bioactivity potential of molecular systems [91][92][93][94][95]. The ligand with a narrower HOMO-LUMO energy gap will also have a higher potential to inhibit the active site of the protein [96,97].…”
Section: Computer Aided Drug Designmentioning
confidence: 99%